Penerapan Metode Prototipe pada Perancangan Aplikasi Smart Farming Sicinamons Berbasis Mobile - Ismail, Agus Yadi; Andayani, Sri Ayu; Nainggolan, Mai Fernando (Universitas Katolik Santo Thomas Medan, 2025)
Smart Farming is a term used for the implementation of technology in the agricultural sector, both in digital and hardware forms. Cinnamomum Sintoc is a plant that grows in tropical areas with high rainfall. This plant requires an adequate supply of nutrients to continue growing and produce essential oils from the bark. Cinnamomum sintoc is planted with a spacing of approximately 4 x 4 meters to provide sufficient space for growth and develop a wide canopy. This plant requires regular fertilization and watering to maintain the quality of growth in the bark. To ensure stable fertilization and watering and maintain optimal nutritional conditions, a system is needed that can monitor plant growth in real time based on soil nutrient conditions. The system can be a mobile-based application that can move the system around the plant. Thus, an integrated database system is needed to record every fertilization and watering activity of the plant as well as plant growth and provide information on soil nutrient conditions. In this study, a mobile-based application was created using a prototype method that has features that can display soil nutrient information on Cinnamomum Sintoc plants in real time through sensors installed on the plants, commands for fertilization and watering, and record plant growth data based on tree diameter and trunk. With the prototyping technique, developers can collect data and information obtained from observations and direct interactions with Cinnamomum Sintoc farmers objectively. The results of this study are in the form of a prototype application design that uses the Unified Modeling Language (UML) approach. This research can be continued with the development of a mobile-based application that actually uses a microservices architecture. With this system, it is hoped that it can assist farmers in monitoring plant conditions, fertilizing and watering, and monitoring the growth of Cinnamomum Sintoc plants.